2023
DOI: 10.1002/jmv.28753
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics characterization of respiratory viral RNA pathogens in children under five years with severe acute respiratory infection in the Free State, South Africa

Abstract: Prompt detection of viral respiratory pathogens is crucial in managing respiratory infection including severe acute respiratory infection (SARI). Metagenomics nextgeneration sequencing (mNGS) and bioinformatics analyses remain reliable strategies for diagnostic and surveillance purposes. This study evaluated the diagnostic utility of mNGS using multiple analysis tools compared with multiplex real-time PCR for the detection of viral respiratory pathogens in children under 5 years with SARI. Nasopharyngeal swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(154 reference statements)
1
1
0
Order By: Relevance
“…Using RNA-based quantitative sequencing together with a comprehensive and sensitive targeted metagenomic approach capturing over 100 bacterial and viral pathogens, we assessed a broad range of respiratory pathogens in infants with RSV, with the aim of examining disease severity correlates. We found strong genomic evidence for presence of at least one additional virus in 26% of the 433 RSV-infected infants, aligning with reported viral co-detection rates of 10–65% in children of all ages with respiratory infections 12 , 28 34 . This co-detection rate is likely a conservative estimate since our stringent detection criteria would necessarily miss very low viral load co-detection.…”
Section: Discussionsupporting
confidence: 87%
“…Using RNA-based quantitative sequencing together with a comprehensive and sensitive targeted metagenomic approach capturing over 100 bacterial and viral pathogens, we assessed a broad range of respiratory pathogens in infants with RSV, with the aim of examining disease severity correlates. We found strong genomic evidence for presence of at least one additional virus in 26% of the 433 RSV-infected infants, aligning with reported viral co-detection rates of 10–65% in children of all ages with respiratory infections 12 , 28 34 . This co-detection rate is likely a conservative estimate since our stringent detection criteria would necessarily miss very low viral load co-detection.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the limitations, our study highlights the multifaceted nature of the nasopharyngeal virome in ARI, particularly adding to other studies showing the feasibility of deploying mNGS in the limitedresource settings of developing countries [15,49]. However, the discrepancies between mNGS and multiplex PCR raise questions about the value of the Amplisens PCR panel in the clinical management of ARI and punctuate the need for the integration of complementary clinical and laboratory methods to enhance detection accuracy of ARI pathogens [50].…”
Section: Discussionmentioning
confidence: 83%
“…Currently, the use of metagenomic next-generation sequence (mNGS) technology is increasingly prevalent in the clinical diagnosis of infectious diseases, particularly when the etiology is not confirmed by conventional microbiological testing (CMT) or when anti-infective treatment proves ineffective. Several studies have demonstrated that mNGS is highly effective in diagnosing mixed infections, and viruses’ infections ( Carpenter et al., 2019 ; Reyes et al., 2021 ; Mei et al., 2023 ; Ogunbayo et al., 2023 ; Xie et al., 2023 ). Compared to culture and other CMT methods, mNGS has a higher positive rate, sensitivity, and specificity in diagnosing invasive fungal infections (IFA) ( Song et al., 2021 ; Li, 2022 ; Wang et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%